Force‐Reversible and Energetic Indole‐Mg‐Indole Cation‐π Interaction for Designing Toughened and Multifunctional High‐Performance Thermosets. (15th December 2021) - Yang, Li; Li, Yicheng; Du, Mengqi; He, Yiting; Lan, Yang; Yin, Qiang; Zhu, Fanghua; Chang, Guanjun
Abstract: Non‐covalent crosslinking has provided versatile and affordable solutions for the design of tough soft polymer materials, but it is not applied in stiff high‐performance thermosets. Here, the authors report a supramolecular approach for the design of tough high‐performance thermosets by using noncovalent sandwich‐structural indole‐Mg‐indole complexes that act as the force‐reversible and energetic crosslinking points, evading the inherent trade‐off between mechanical strength and ductility for high‐performance thermosets. Compared to traditional epoxy polymer materials, the indole‐Mg‐indole crosslinks of the network enables synchronously enhancement of mechanical strength and ductility owing to the increased interaction‐energy and efficient dissociation and reassociation behaviors given by the dynamic indole‐Mg‐indole complexes, which is quite challenging to achieve by conventional chemical methods. In addition, local manipulation of crosslinking confers the resulting thermosets with multiple fast stimuli‐responsive functions, such as recyclability, healability, and adhesion. Abstract : Force‐reversible high‐performance thermosets are prepared using indole‐Mg‐indole cation‐π interaction as crosslinking. The energetic indole‐Mg‐indole interaction can be reversibly installed and removed by force perturbation at ambient conditions, making these thermosets with excellent mechanical properties and multiple stimuli‐responsive functions, such as recyclability, healability, and adhesion.